2004
DOI: 10.1111/j.1747-5457.2004.tb00043.x
|View full text |Cite
|
Sign up to set email alerts
|

ORGANIC FACIES, DEPOSITIONAL ENVIRONMENT AND PETROLEUM GENERATING CHARACTERISTICS OF THE LACUSTRINE SHAHEJIE FORMATION, ES4 MEMBER, WESTERN DEPRESSION, LIAOHE BASIN (NE CHINA)

Abstract: presence of Botryococcus braunii telalginite. The abundance of lycopane and its aromatised diagenetic analogues confirmed the presence of this algal species. Generally low concentrations of gammacerane and high pristane/phytane ratios indicate a low salinity, hydrologically open environment in which oxic conditions generally prevailed, resulting in relatively poor preservation of OM.Sediments of poor source rock quality deposited in the marginal fan-delta setting (the Shu-Du area) can be distinguished visually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 70 publications
2
20
0
Order By: Relevance
“…On the other hand, the extrapolation is also comparable to geological predictions for thermally less stable lacustrine samples (e.g. from wells AP24: Anvil Points 24 gal/ton and GOVT: Government 33-4 from the Uinta Basin) published in Braun et al (1991), which exhibit calculated T max values between 147 and 149 °C, as well as for lacustrine type I samples from the ES4 member of the Shahejie Formation in the Western Depression of the Liaohe Basin, NE China, published in Fuhrmann et al (2004), which exhibit calculated T max values between 148 and 159 °C.…”
Section: Lability Of Organic Matter (Bulk Kinetic Parameters)supporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the extrapolation is also comparable to geological predictions for thermally less stable lacustrine samples (e.g. from wells AP24: Anvil Points 24 gal/ton and GOVT: Government 33-4 from the Uinta Basin) published in Braun et al (1991), which exhibit calculated T max values between 147 and 149 °C, as well as for lacustrine type I samples from the ES4 member of the Shahejie Formation in the Western Depression of the Liaohe Basin, NE China, published in Fuhrmann et al (2004), which exhibit calculated T max values between 148 and 159 °C.…”
Section: Lability Of Organic Matter (Bulk Kinetic Parameters)supporting
confidence: 82%
“…The frequency factor of the more heterogeneous sample 1 (3.84E + 14 s −1 ) is also lower than those of samples 2-4 (1.12E + 15 to 5.30E + 15 s −1 ) indicating a lower thermal stability. With respect to the broader E a distribution of sample 1, it should be noted that heterogeneous (broad E a distributions) as well as homogeneous (single E a ) type I kerogens are found in lacustrine settings, as reported, for example, in the Laney Shale and Luman Tongue of the Green River Shale (Horsfield et al 1994) or in the ES4 member of the Shahejie Formation in the Western Depression of the Liaohe Basin, NE China (Fuhrmann et al 2004). It is clear that kinetic parameters vary appreciably, even within lacustrine settings, and therefore, evaluations should be conducted on a case-by-case basis.…”
Section: Lability Of Organic Matter (Bulk Kinetic Parameters)mentioning
confidence: 78%
“…However, Adam et al (2006) reported a C 40 monoaromatic lycopane derivative in the extractable hydrocarbons of the Messel oil shale and proposed that it can be used as a specific biomarker for race L in sediments deposited under freshwater and/or brackish conditions (Derenne et al, 1994;Grice et al, 1998;Adam et al, 2006;Volkman, 2014). The lipids from B. braunii race L appear to be restricted to sediments from the Eocene or younger (Derenne et al, 1994;Grice et al, 1998;Fuhrmann et al, 2004;Adam et al, 2006;Volkman, 2014), although there is one report of a C 40 monoaromatic hydrocarbon apparently related to lycopane in a Permian sediment (Kluska et al, 2013) and the same series of C 40 hydrocarbons and ketone identified in the algaenan of the L race was reported in the pyrolysate of a Cenomanian black shale (Salmon et al, 1997). In neither case could an origin from Botryococcus be confirmed due to the lack of morphological remains and a source other than Botryococcus is possible (Volkman, 2014).…”
Section: B Braunii Biomarkersmentioning
confidence: 94%
“…Similar source rocks are also important source rocks in other subunits of the Bohai Bay basin such as in the West Liaohe depression (Fuhrmann et al, 2004). However, high-wax oils have not been found in significant volumes elsewhere in the Bohai Bay basin.…”
Section: Discussionmentioning
confidence: 98%